2023
DOI: 10.1177/03635465231153165
|View full text |Cite
|
Sign up to set email alerts
|

Current Definitions of Failure in Lateral Ankle Instability Surgery: A Systematic Review

Abstract: Background: “Failure” is a term that is frequently used to describe an unfavorable outcome for patients who undergo surgical treatment for lateral ankle instability (LAI). A standard definition of failure for the surgical treatment of ankle instability has not been established by clinicians and researchers. Purpose: To identify the definitions of ankle instability treatment failure that are currently in the literature and to work toward the standardization of the definition. Study Design: Systematic review; Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…These patients were not considered failures because we defined failure as recurrent instability, no improvement, an AOFAS score <79 or KAFS ≤80. We adopted both Nery's 29 definition of failure as an AOFAS score <79 and that reported by Dallman et al 11 systematic review that found failure in CLAI surgeries was most commonly defined as recurrent instability (in 40% of studies published between 1984 and 2021). All of the individuals evaluated in this study had isolated ATFL lesions; however, concurrent ATFL and CFL lesions may not be a contraindication for this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were not considered failures because we defined failure as recurrent instability, no improvement, an AOFAS score <79 or KAFS ≤80. We adopted both Nery's 29 definition of failure as an AOFAS score <79 and that reported by Dallman et al 11 systematic review that found failure in CLAI surgeries was most commonly defined as recurrent instability (in 40% of studies published between 1984 and 2021). All of the individuals evaluated in this study had isolated ATFL lesions; however, concurrent ATFL and CFL lesions may not be a contraindication for this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review in this month’s issue of the American Journal of Sports Medicine illustrates this phenomenon in the ankle instability literature. 4 The authors sifted through 1200 articles from 5 databases and ultimately examined 42 articles that reported failure in the surgical treatment of lateral ankle instability. Of these studies, 30 were case series and 27 focused on nonathletes.…”
mentioning
confidence: 99%